Balance confidence scale: Preliminary validity, reliability, and relation to neural excitability in young adults. (July 2019) - Nandi, Tulika; Lewthwaite, Rebecca; Fisher, Beth E.; Salem, George J.
Abstract: Balance confidence may reflect and affect balance performance, and this effect may be mediated by neural inputs to muscles. Available balance confidence scales are designed for older adults and individuals with pathological conditions. To eliminate ceiling effects for young adults and to enable the study of neural excitability in relation to confidence relevant to balance, we developed a Balance Confidence Scale (BCS), comprised of items depicting single limb stance conditions of varying difficulty. Motor cortical excitability was measured using transcranial magnetic stimulation (TMS). Preliminary construct validity was examined relative to balance performance, perceived steadiness, and previous physical activity in 20 young adults (25.7 ± 4.2 years; 11 females). The scale showed good internal consistency (Cronbach's α = 0.81) and good test-retest reliability (ICC2, 1 = 0.84) in a separate sample of 21 young adults (23.8 ± 4.6 years; 11 females). Balance confidence ranged from 34 to 79.6% in the validity sample. Confidence was correlated with performance indexed using center of pressure velocity (r = −0.62, p = 0.01) and area (r = −0.49, p = 0.04), in a relatively difficult standing condition with one leg positioned on an unstable spring. Perceived steadiness and overall physical activity were not correlated with confidence; however, participants with higher confidence scores reported greater experience with balance-related activities. Finally, confidence was related to indices of motor cortical excitability. The Balance Confidence Scale has sound preliminary validity and reliability and holds promise for the study of neural processes mediating social-cognitive influences on balance performance. Highlights: Balance Confidence Scale (BCS) is a valid and reliable tool. BCS is suitable for healthy and athletic populations. M1 excitability partially mediates effect of confidence on performance.